STRATEGI DAN PENGELOLAAN RISIKO PEMBIAYAAN PADA PT (PERSERO) PEGADAIAN KC KEDUNG HALANG UNIT SALABENDA BOGOR - Listiawati, Rodiana; Suryani, Heti Fitri; Sukimin, Dini Ayuning Ratri; Farhani, Nuraeni Hadiati; Redyanita, Hastuti (Jurnal Abdi Insani, 2025)
The development of non-bank financial institutions in the economy is increasing, one of which is the presence of Pegadaian as a financial institution that provides loan facilities with certain collateral. The problem faced by PT Pegadaian is the increase in defaults and bad debts of customers or non performing loan. This condition is often caused by deliberate actions of customers in fulfilling their obligations, as well as a mismatch between the use of credit funds with the planned goals. Based on the above conditions, the community service team will provide assistance regarding financial literacy and managing healthy debt for pawnshop customers. The purpose of this community service activity is that the Community Service Team will conduct socialization to increase financial literacy through the introduction of pawnshop products through the introduction of financing products, especially non-pawnshop products of PT Pegadaian CP Kedunghalang. The success of this community service activity through assistance can be seen when customers have better financial planning and PT Pegadaian can provide appropriate and targeted credit and there is an increase in understanding between before and after the material is delivered through the provision of Pre-Tests and Post-Tests with result 29% raised.